Tahrekey pakistan k rehnumah - Imran, maqsood (Ferozesons; pakistan, 2009)
"Tahrekey Pakistan ke Rehnuma" offers a detailed account of the prominent leaders and visionaries who played a pivotal role in Pakistan's independence movement, highlighting their contributions, struggles, and leadership in shaping the nation's destiny.